Progress in research into the genes associated with venous thromboembolism - Zhao, Lian-xing (World J Emerg Med, 2015)
BACKGROUND: Venous thromboembolism (VTE), including both deep vein thrombosis (DVT) and pulmonary embolism (PE), is a common, lethal disorder that affects hospitalized and non-hospitalized patients. This study aimed to review the progress in the research into VTE. DATA SOURCES: We reviewed the studies about VTE and verified different genetic polymoriphisms of VTE. RESULTS: The pathogenesis of VTE involves hereditary and acquired factors. Many studies indicated that the disorder of coagulation and fibirnolytic system is of utmost importance to this disease. Genetic polymoriphism-related VTE demonstrated significant differences among geographies and ethnicities. CONCLUSION: VTE has many risk factors, but genetic factors play an important role.